Living in the environment : principles, connections, and solutions - Miller, G. Tyler (George Tyler), 1931-; Spoolman, Scott (Belmont, CA : Brooks/Cole, 2012)
Three principles of sustainability, solar energy, chemical cycling, and biodiversity, can guide us in making a shift to a more sustainable society. Five major subthemes - natural capital, natural capital degradation, solutions, trade-offs, and the fact that individuals matter - guide the way to sustainability. This book looks at these subthemes and builds on the knowledge you learn by providing core case studies.
Humans and sustainability : an overview - Science, ecological principles, and sustainability - Sustaining biodiversity - Sustaining natural resources - Sustaining environmental quality - Sustaining human societies - Supplements - Glossary - Index.
Includes glossary and index.
Keywords: Environmental sciences -- Textbooks; Human ecology -- Textbooks; Pollution -- Textbooks; Sustainable development -- Textbooks